Chapter 1 Presence, Museums, and Immersive Technologies An Interdisciplinary Exploration - Shehade, Maria (Taylor & Francis, 2024)
Recently there has been a re-articulation of the concept of 'presence', which has evolved into an important trend in the humanities. Despite the many cross-disciplinary endeavours to define what 'presence' is, it proves a rather elusive concept, with different conceptualisations of the term found across different disciplines. In museum studies, presence is associated with the type of experience that a visitor can have in a museum setting, in an attempt to find the balance between interpretation/meaning and embodiment/immersion in the museum space. The rapid advancement of technology and the turn towards immersive experiences in museums, however, has raised a set of new questions regarding the effects of technology on presence. The aim of this chapter is to provide a multidisciplinary discussion of the concept of presence and critically explore the different approaches to it to pinpoint the limitations and gaps in existing literature. The chapter explores the dichotomy between presence and meaning effects and the application of presence in museum environments with an emphasis on embodiment, affect and atmosphere. It also investigates how presence is defined and studied in computer science. The ultimate aim of this chapter is to provide the theoretical basis for the exploration of the potential role of technologies as facilitators of presence in museums.